Augmented reality for anatomy course for children with autism - Misael Lazo-Amado; Laberiano Andrade-Arenas (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
Autism spectrum disorder (ASD) that mainly affects social interaction and effective communication, showing problems in their learning, reflected in the lack of attention in schools, such as in anatomy classes. The main objective of the project is to develop a mobile application for children with autism to improve their learning in Anatomy and social interaction through augmented reality (AR). The methodology to be used is ADDIE which is in charge of analyzing the experience of the work team to find the ease of software development, proposing the efficient development with continuous improvement according to the evaluation to the specialists. The results show the evaluation of the specialists on the mobile application with AR where they will indicate their satisfaction with the application. In conclusion, it will be shown a mobile application with AR that offers a technological and eye-catching novelty for users in order to improve the educational development of children with autism spectrum disorder.